Lipid Accumulation in Dysferlin-Deficient Muscles - Grounds, M.; Terrill, J.; Crabb, Hannah; Robertson, Terry; Papadimitriou, J.; Spuler, S.; Shavlakadze, T. (Elsevier Inc., 2014)
Dysferlin is a membrane associated protein involved in vesicle trafficking and fusion. Defects in dysferlin result in limb-girdle muscular dystrophy type 2B and Miyoshi myopathy in humans and myopathy in A/Jdys/ and BLAJ mice, but the pathomechanism of the myopathy is not understood. Oil Red O staining showed many lipid droplets within the psoas and quadriceps muscles of dysferlin-deficient A/Jdys/ mice aged 8 and 12 months, and lipid droplets were also conspicuous within human myofibers from patients with dysferlinopathy (but not other myopathies). Electron microscopy of 8-month-old A/Jdys/ psoas muscles confirmed lipid droplets within myofibers and showed disturbed architecture of myofibers. In addition, the presence of many adipocytes was confirmed, and a possible role for dysferlin in adipocytes is suggested. Increased expression of mRNA for a gene involved in early lipogenesis, CCAAT/enhancer binding protein-δ, in 3-month-old A/Jdys/ quadriceps (before marked histopathology is evident), indicates early induction of lipogenesis/adipogenesis within dysferlin-deficient muscles. Similar results were seen for dysferlin-deficient BLAJ mice. These novel observations of conspicuous intermyofibrillar lipid and progressive adipocyte replacement in dysferlin-deficient muscles present a new focus for investigating the mechanisms that result in the progressive decline of muscle function in dysferlinopathies.